Effect of Absorbent Type on the Absorption Durability of Biogas Purification - Fitrah Guna Muhammad; Muhammad Watsieq Ibadurrahman; Rachmad Ramadhan Yogaswara; Novel Karaman; Suprihatin Suprihatin; Sani Sani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Biogas purification is essential to increase methane concentration and reduce impurities such as carbon dioxide and hydrogen sulfide, which decrease calorific value and cause corrosion in energy systems. This study evaluates the effect of absorbent solution type on biogas purification efficiency and absorption durability using chemical absorption methods. Alkaline solutions including sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)?), and their binary mixtures were employed at a concentration of 20% (w/v). Biogas derived from molasses fermentation was passed through bubble column absorbers and analysed using an Orsat apparatus over 2–10 days of absorption. Results show that all absorbents significantly increased methane concentration while reducing CO? and H?S. The highest methane concentration of 86.75% was achieved using KOH on day four, exceeding the Indonesian biogas quality standard (SNI 8019:2014). Absorbent saturation occurred after approximately six days, indicated by declining purification performance. These findings confirm that chemical absorption using alkaline solutions is effective for biogas upgrading, with KOH demonstrating the best overall performance and durability. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 15: Life on Land